CLAUSAL AND COMMUNICATIVE UNITS OF SPEECH - Verdonik, Darinka (Slavia Centralis, 2026)
The paper stems from the aim of identifying boundaries between units that express illocutionary force in spoken Slovenian—or, as the concept is termed in some corpus annotation frameworks, dialogue acts. In the search for an appropriate unit, the analysis draws on the syntactic structure of spoken language and focuses on the problem of defining clausal and communicative units. Among the findings, it highlights the necessity of considering auditory perception in unit delimitation and questions the reliability of existing definitions.
Keywords: speech act; prosody; clause; syntax